2006
DOI: 10.1093/hmg/ddl201
|View full text |Cite
|
Sign up to set email alerts
|

Laminin α1 chain improves laminin α2 chain deficient peripheral neuropathy

Abstract: Absence of laminin alpha2 chain leads to a severe form of congenital muscular dystrophy (MDC1A) associated with peripheral neuropathy. Hence, future therapies should be aimed at alleviating both muscle and neurological dysfunctions. Pre-clinical studies in animal models have mainly focused on ameliorating the muscle phenotype. Here we show that transgenic expression of laminin alpha1 chain in muscles and the peripheral nervous system of laminin alpha2 chain deficient mice reduced muscular dystrophy and largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 39 publications
6
57
0
Order By: Relevance
“…The Lma2 deficient mice provide models of the nerve pathology seen in human MDC1A congenital muscular dystrophy. The deficiency state phenotype was found to be corrected by transgenic expression of the homologous laminin a1 subunit, a genetic rescue that was only partially dependent on the presence of the LG4-5 domains (Gawlik et al 2006;Gawlik et al 2010).…”
Section: Peripheral Nerve Axonal Envelopment and Myelinationmentioning
confidence: 99%
“…The Lma2 deficient mice provide models of the nerve pathology seen in human MDC1A congenital muscular dystrophy. The deficiency state phenotype was found to be corrected by transgenic expression of the homologous laminin a1 subunit, a genetic rescue that was only partially dependent on the presence of the LG4-5 domains (Gawlik et al 2006;Gawlik et al 2010).…”
Section: Peripheral Nerve Axonal Envelopment and Myelinationmentioning
confidence: 99%
“…From 1994, knock-out mouse or spontaneous mutant mouse strains have been identified as animal models for MDC1A with total and partial deficiency [99][100][101][102][103][104][105] , and experimental therapeutic strategies have been attempted 102,103,[106][107][108][109][110][111][112][113][114][115][116] . In mice, Kuang et al 102,103 were successful in obtaining the expression of a human laminin alpha 2 chain transgene under the regulation of a muscle-specific creatine kinase promoter.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Therefore, a future therapeutic attempt for patients with MDC1A could be the combination of antiapoptotic drugs with the expression of mini-agrin in muscle, and/or the up-regulation of endogenous agrin. Gawlik et al [110][111][112] generated laminin alpha-2 deficient mice expressing laminin alpha-1 in peripheral nerves and muscles. Dy 3K /dy 3K mice harboring the laminin alpha-1 transgene in these tissues presented reduced muscular dystrophy and show peripheral myelination.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%
“…Previous studies showed that the peripheral neuropathy phenotypes are alleviated exclusively in transgenic mice that overexpress Lama1 not only in the skeletal muscle, but also in the nerves 7 . We observed expression of Lama1 in the endoneurium of sciatic nerves in the treated mice (Fig.…”
Section: E)mentioning
confidence: 99%